Islamic Philosophy A-Z: By Peter S. Groff with Oliver Leaman (Edinburgh, United Kingdom: Edinburgh University Press, 2007. 237 pages.) (American Journal of Islam and Society, 2008)
Understanding Islamic philosophy, an indispensable formative link in thechain of medieval thought, is crucial to grasping the intertwined developmentof philosophical ideas both within and without the Islamic sphere duringthe period under discussion. Peter Groff and Oliver Leaman’s textbelongs to the discipline of the philosophical and theological analysis ofIslam. It is an attempt to shed some light on the essential, mainly Islamiccontribution to the philosophical thought of the Middle Ages. This workintends to offer “the vital insights and resources of the Islamic philosophicaltradition” (p. xi) as a main influence upon medieval philosophic thought indifferent religions (Judaism and Christianity) and cultures (India).Furthermore, he rightfully refers to Islamic philosophy as a transmitter of theclassical Greek legacy.This concise work contains brief entries (alphabetically ordered), keyterms, bold marked cross-references to related terms for easy access, andmajor figures in the rich heritage of Greek, Jewish, Christian, and Muslimphilosophy. Each brief entry is written in a very comprehensible style andcovers the main relevant ideas related to the theme being discussed. Sincereligion has always played a decisive role in the development of Islamicthought and was never separated from the state, it is also present in varyingdegrees in nearly all of the entries. Consequently, this work provides informationon the development of Islamic belief. The bibliographical referencesfor further reading at the end of each entry are very helpful, though mostlylaconic. Key concepts or terms are given in a simplifiedArabic transcriptionthat differs from the standard one ...